Theoretical and Practical Aspects of Financing the Road Economy in the Supply Chain Strategy of Russian Federation - Elena V. Konvisarova; Tatiana A. Levchenko; Artem A. Pustovarov (International Journal of Supply Chain Management, 2019)
Currently the development of transport infrastructure and the road economy is an important part of supply chain policy allowing providing higher rates and quality of economic growth. However it is impossible to make it without competent definition of financing sources of the road economy. The analysis of funding mechanisms for road economy and practice of their use as well as defining the measures for improvement of the operating system of financing acted as a research objective. When carrying out a research the set of scientific methods was used: analysis and synthesis, system approach, comparison, abstraction, historical method, induction and deduction, generalization and formalization. Authors carried out classification of funding mechanisms for road economy, their merits and demerits are revealed. The carried-out analysis of processes of financing the road economy in Russia for the last ten years is showed, on one hand, growth of volumes of road construction connected with revival of road funds, creation of state programs in this sphere, on the other hand, insufficiency of the allocated funds, incomplete compliance of the operating system of financing the road economy of Russia to priorities of development of the economy is showed. Authors connect the reasons of it with shortcomings of the operating system of financing the road economy. In work the package of measures for elimination of shortcomings is defined. As those development of target financing through the three-level system of road funds, integration of municipal road funds, establishment of interrelation between consumption of the road and a payment for its use, activation of processes of attraction of private investments on projects of public-private partnership is offered what requires lifting of restrictions for distribution at the regional level of the best federal practice. Theoretical and methodical results of a research can be used in the course of financial security of the state impact on economic development.